Reduction of unwanted submental fat with ATX‐101 (deoxycholic acid), an adipocytolytic injectable treatment: results from a phase III, randomized, placebo‐controlled study3. (February 2014) - Rzany, B.; Griffiths, T.; Walker, P.; Lippert, S.; McDiarmid, J.; Havlickova, B.
Summary Background Unwanted submental fat (SMF) is aesthetically unappealing, but methods of reduction are either invasive or lack evidence for their use. An injectable approach with ATX‐101 (deoxycholic acid) is under investigation. Objectives To evaluate the efficacy and safety of ATX‐101 for the reduction of unwanted SMF. Methods In this double‐blind, placebo‐controlled, phase III study, 363 patients with moderate/severe SMF were randomized to receive ATX‐101 (1 or 2 mg cm−2) or placebo injections into their SMF at up to four treatment sessions 28 days apart, with a 12‐week follow‐up. The co‐primary efficacy endpoints were the proportions of treatment responders [patients with ≥ 1‐point improvement in SMF on the 5‐point Clinician‐Reported Submental Fat Rating Scale (CR‐SMFRS)] and patients satisfied with their face and chin appearance on the Subject Self‐Rating Scale (SSRS). Secondary endpoints included skin laxity, calliper measurements and patient‐reported outcomes. Adverse events were monitored. Results Significantly more ATX‐101 recipients met the primary endpoint criteria vs. placebo: on the clinician scale, 59·2% and 65·3% of patients treated with ATX‐101 1 and 2 mg cm−2, respectively, were treatment responders vs. 23·0% for placebo (CR‐SMFRS; P < 0·001); on the patient scale, 53·3% and 66·1%, respectively, vs. 28·7%, were satisfied with their face/chin appearance (SSRS; P < 0·001). Calliper measurements showed a significant reduction in SMF (P < 0·001), skin laxity was not worsened and patients reported improvements in the severity and psychological impact of SMF with ATX‐101 vs. placebo. Most adverse events were transient and associated with the treatment area. Conclusions ATX‐101 was effective and well tolerated for nonsurgical SMF reduction.